Long-term Room Temperature Instability in Thermal Conductivity of InGaZnO Thin Films. Issue 22 (22nd February 2016) - Cui, Boya; Buchholz, D. Bruce; Zeng, Li; Bedzyk, Michael; Chang, Robert P. H.; Grayson, Matthew
ABSTRACT: The cross-plane thermal conductivities of InGaZnO (IGZO) thin films in different morphologies were measured on three occasions within 19 months, using the 3ω method at room temperature 300 K. Amorphous (a-), semi-crystalline (semi-c-) and crystalline (c-) IGZO films were grown by pulsed laser deposition (PLD), followed by X-ray diffraction (XRD) for evaluation of film quality and crystallinity. Semi-c-IGZO shows the highest thermal conductivity, even higher than the most ordered crystal-like phase. After being stored in dry low-oxygen environment for months, a drastic decrease of semi-c-IGZO thermal conductivity was observed, while the thermal conductivity slightly reduced in c-IGZO and remained unchanged in a-IGZO. This change in thermal conductivity with storage time can be attributed to film structural relaxation and vacancy diffusion to grain boundaries.